Lake-level changes in the past 50 ka reconstructed from the lacustrine delta deposits in Kathmandu Valley, Nepal - Sakai, Tetsuya; Gajurel, Ananta P; Tabata, Hideo; Ooi, Nobuo; Upreti, Bishal N (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1314 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.129